Profissional de apoio: práticas colaborativas com ênfase inclusiva no espaço escolar - Portalette, Vania Fernanda Gulart (2017)
Research linked to the Master Professional Course of the Postgraduate Program in Public Policies and Educational Management of the Federal University of Santa Maria, in the line of Pedagogical Management in Educational Contexts. It aims to understand the presence and specificities of the support professional for the school inclusion of students with disabilities. The investigative course assumed aspects of qualitative research based on the search for data that meets the research objective. Theoretical references permeated the legal documents and scientific productions that give rise to the discussion about the work of the support professional, the training of teachers and the paths of inclusive education. In the field research, participant observation, logbook and semi-structured interview with the support professionals of a school in the municipal network of Santa Maria were used. The analysis of the findings was based on the categorization technique, where it was found that the categories relate to teaching practices, pedagogical support and training to act as a support professional. It is concluded that the teachers who work in the municipality of Santa Maria understand that the support professional carries out teaching practices with the target public students of special education, that support professionals perceive their role in the inclusion of students with disabilities As a pedagogical support. It is necessary that these support professionals undergo a formative process to work with the students characterized as the target audience of special education. Thus, the construction of a Training Reference for support professionals working in the municipal network of Santa Maria was characterized as the product of this professional master's research.